Narrative Unreliability in The Good Soldier: A Tale of Passion - Şule Okuroğlu Özün (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
The Good Soldier: A Tale of Passion (TGS) by Ford Maddox Ford is one of the earliest examples of the Modernist Period in English Literature. Written in 1915 and set just before the Great War, the novel is about two couples, an aristocratic English couple (Edward and Leonora Ashburnham) and a wealthy American couple (John and Florence Dowell), who meet at a spa in Nauheim, Germany in 1904. John Dowell, as the involved first-person narrator, tells the story that revolves around Edward’s and Florence’s inability to remain faithful to their partners, Edward’s love affair with several women, Edward’s refusal to give up his idealized dream of living as a Victorian gentleman, and John Dowell’s struggle with how to interpret and narrate all these events. Although the themes of the novel are like typical Victorian issues, unlike its Victorian predecessors, the novel lacks omniscient narration and depends on frequent shifting of emotional impressions and views of its narrator. Thus, what makes the novel interesting and its interpretation difficult is the unconventional narrator who brings impressionistic storytelling into play as a narrative technique, and who, for the readers, offers this method as an alternative to changing social order, personal integrity and conventional novel form. The aim of this paper is to discuss how Dowell’s unreliable narrative technique creates a mimetic illusion which makes the reader an active participant in Dowell’s writing of the story.